2015
DOI: 10.1021/nn505639q
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Strongly Fluorescent Graphene Quantum Dots by Cage-Opening Buckminsterfullerene

Abstract: Graphene quantum dots is a class of graphene nanomaterials with exceptional luminescence properties. Precise dimension control of graphene quantum dots produced by chemical synthesis methods is currently difficult to achieve and usually provides a range of sizes from 3 to 25 nm. In this work, fullerene C60 is used as starting material, due to its well-defined dimension, to produce very small graphene quantum dots (∼2-3 nm). Treatment of fullerene C60 with a mixture of strong acid and chemical oxidant induced t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
145
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 262 publications
(159 citation statements)
references
References 33 publications
11
145
0
Order By: Relevance
“…1d) confirmed that the as-prepared UFQDs had a relatively narrow size distribution with <2RH> 3.5 ± 1.0 nm, in agreement with the data of Ref. [38] and in reasonable agreement with the expected dimensions of monodisperse unfolded fullerene. Comparable PL quenching effects, with different values of sensitivity to the ion concentration, were also observed in the presence of Pb 2+ and As(III) (Figs.…”
Section: Optical Characterization Of Ufqdssupporting
confidence: 89%
See 4 more Smart Citations
“…1d) confirmed that the as-prepared UFQDs had a relatively narrow size distribution with <2RH> 3.5 ± 1.0 nm, in agreement with the data of Ref. [38] and in reasonable agreement with the expected dimensions of monodisperse unfolded fullerene. Comparable PL quenching effects, with different values of sensitivity to the ion concentration, were also observed in the presence of Pb 2+ and As(III) (Figs.…”
Section: Optical Characterization Of Ufqdssupporting
confidence: 89%
“…1a) were similar to those of Ref. [38] and, along with the absorption curve and the dependence of the emission peak on the excitation wavelength (Fig. 1b,c), showed the characteristic spectral features found in regular GOQDs synthesized from graphite or citric acid [28][29][30][31][32][33][34] [35].…”
Section: Optical Characterization Of Ufqdssupporting
confidence: 81%
See 3 more Smart Citations